Ecolinguistics in the Grain Lexicon of Mandailing Language - Dharmawati; Dwi Widayati (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2021)
The research discusses the study of ecolinguistics in the grain lexicon of the Mandailing language. The purpose of this study was to describe the grain lexicon in the Mandailing community. This research is a qualitative descriptive study using an ecolinguistic approach. This research conducted inManisak Village, Batang Natal District, Madina Regency (Mandailing Natal). The subjects of this study were native speakers of the Mandailing language in Manisak village. The source of this research data is grain speech in the Mandailing community. The data collection technique was carried out by the listening method which began with observation and interviews. The results of this study are first, the acquisition of the grain lexicon found in the Mandailing community in the form of words and phrases. Second, the resulting lexicon refers to three classifications, namely lexicon related to activities or ways of working (verb), lexicon related to material (noun) and lexicon related to nature (ejective).